2022
DOI: 10.3390/pharmaceutics14030535
|View full text |Cite
|
Sign up to set email alerts
|

pH-Responsive Nanoparticles for Delivery of Paclitaxel to the Injury Site for Inhibiting Vascular Restenosis

Abstract: A high incidence of restenosis has been reported at the site of inflammation following angioplasty and stent implantation. The anti-proliferative drug paclitaxel (PTX) could help to reduce inflammation and restenosis; however, it has poor water solubility and serious adverse side effects at high doses. Given the presence of metabolic acidosis at the site of inflammation, we hypothesized that nanoparticles that are responsive to low pH could precisely release the loaded drug at the target site. We successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Placement of the stent within the blood vessel leads to biocompatibility issues caused by its foreign body properties (Zhu et al, 2022). To tackle this issue, experiments related to blood compatibility were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of the stent within the blood vessel leads to biocompatibility issues caused by its foreign body properties (Zhu et al, 2022). To tackle this issue, experiments related to blood compatibility were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…PLGA NPs, approved by the US FDA, have been extensively developed and used as drug delivery vehicle and diagnostics in CVDs [ 47 , 48 ]. For instance, the delivery of NPs loaded with anti-proliferative agent after percutaneous transluminal coronary angioplasty or balloon angioplasty to treat restenosis [ 49 , 50 , 51 ]. Moreover, due to its ease of surface conjugation with the chemical reactions, the PLGA NPs are a suitable candidate for anchoring HuscFv with controlled conjugation orientation [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our fabricated material is considered as submicron material with sizes ranging from 100 nm–1 µm [ 60 ]. However, according to several nanomaterial studies, they also reported polymeric NPs with sizes larger than 100 nm [ 49 , 52 ]. Therefore, the polymeric particles in the present study were represented as NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Another group designed PLGA nanoparticles functionalized with encapsulated sodium bicarbonate to selectively release paclitaxel following particle disintegration triggered by low pH associated with metabolic acidosis at the site of atherosclerotic inflammation. 119 Polyurethanes are similarly readily degradable and have been used in several formulations to produce redox-responsive nanoparticles that target aortic endothelium and atherosclerotic plaque. These polyurethane-based particles have been used in ligand-receptor targeting strategies using glycoprotein and anti-CD34 antibodies to locally outcompete platelet aggregation on injured endothelium and capture circulating endothelial progenitor cells to limit inflammation and promote in situ vessel repair.…”
Section: Advancements In Excipientsmentioning
confidence: 99%